Determinan Keberhasilan Pemicuan Stop Buang Air Besar Sembarangan di Wilayah Kerja Puskesmas Busalangga Kecamatan Rote Barat Laut Kabupaten Rote Ndao - Teni Lesik; Marylin S. Junias; Petrus Romeo (Universitas Nusa Cendana, 2021)
The behavior of open defecation is still a problem of health behavior in Indonesia. The purpose of this study was to determine and analyze the determinants of successful triggering of open defecation in the working area of ​​Busalangga Public Health Center, Rote Barat Laut District, Rote Ndao Regency in 2020. The type of research used was analytic observational with cross sectional design. The population in this study were all heads of households in the villages of Tualima, Temas, Modosinal and Busalangga who had or had been exposed to the Community-Based Total Sanitation (STBM) program, totaling 1,165 families. The sample in this study were 92 families selected by simple random sampling technique. Methods of data analysis using Chi-Square analysis. The results showed that there was a relationship between knowledge and the success of triggering stopping BABS (p-value=0.004), latrine ownership (p-value=0.005), availability of clean water (p-value=0.023), the role of health workers (p-value=0.014), and support from village officials (p-value=0.044). The success of determining the triggering of stopping open defecation in the working area of ​​the Busalangga Community Health Center is influenced by knowledge, ownership of latrines, availability of clean water, the role of health workers, and the support of good village officials, so it is hoped that the community will continue and continue to improve health behavior related to stopping open defecation so that people can avoid health problems that arise from unhealthy behavior and also people must continue to seek health information to add insight and knowledge.